2010
DOI: 10.5737/1181912x2026674
|View full text |Cite
|
Sign up to set email alerts
|

Identifying supportive care needs of women with ovarian cancer

Abstract: Women diagnosed with ovarian cancer may experience many shortterm and long-term effects from cancer and its treatment. Cancer has more than a physical impact, yet there is a lack of information about the types of needs these women have and whether they want help in meeting their needs.The main purpose of this cross-sectional, descriptive study was to identify the supportive care needs (physical, emotional, social, informational, spiritual, psychological and practical) Ovarian cancer is the fourth leading cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
2
30
1
1
Order By: Relevance
“…Of the 30 included studies, nine were conducted in Australia [16][17][18][19][20][21][22][23][24], five in the USA [11,[25][26][27][28], four in Taiwan [29][30][31][32], three in the UK [33][34][35], three in Canada [36][37][38], two in the Netherlands [39,40], and one each in Sweden [41], Germany [42], Finland [43], and Singapore [44]. Table 1 shows the characteristics of the included studies.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 30 included studies, nine were conducted in Australia [16][17][18][19][20][21][22][23][24], five in the USA [11,[25][26][27][28], four in Taiwan [29][30][31][32], three in the UK [33][34][35], three in Canada [36][37][38], two in the Netherlands [39,40], and one each in Sweden [41], Germany [42], Finland [43], and Singapore [44]. Table 1 shows the characteristics of the included studies.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Two studies showed that despite reporting a need, not all patients wanted help with that need from a healthcare professional [25,37]. It was suggested that this might be due to unfamiliarity with available treatment options.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Little information is available about the specific needs of women with ovarian cancer. The only published study to date, a cross-sectional single clinic sample of 50 women, reported that the most frequently reported needs were psychosocial, such as fear about the cancer returning or spreading [6]. While other studies include women with ovarian cancer among heterogeneous gynecological samples, these have been cross-sectional, mainly longer-term survivors [7][8][9] and/or convenience samples [9,10] and do not separately report on women with ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our participants noted that nurses need to assess and know about different aspects of patients' health and lives. The results of a study in Canada also showed that cancer has different short-and long-term effects on physical, social, and psychological aspects of patients' lives (31). Accordingly, paying attention to different aspects of their lives would minimize the negative effects of cancer on patients' lives and improve their quality of life (32).…”
Section: Discussionmentioning
confidence: 99%